Polysomnographic study in pediatric neurofibromatosis type 1 - Carotenuto, Marco; Messina, Giovanni; Esposito, Maria; Santoro, Claudia; Iacono, Diego; Spruyt, Karen (Frontiers in Neurology, 2023)
Background Neurofibromatosis type 1 (NF1) is a genetic disease that alters neurodevelopment. We aimed to analyze the sleep macrostructure of a sample of children affected by NF1 without neurocognitive co-morbidities and MRI reports of unidentified bright objects (UBOs). Methods A 100 pre-pubertal children participated in the cross-sectional study: 50 subjects were children diagnosed with NF1 and 50 subjects were typically developing healthy children (TDC). All participants underwent polysomnographic evaluation through which conventional sleep parameters were collected: Total sleep time (TST), Sleep latency (SOL), first REM latency (FRL), number of stage shifts/h (SS/h), number of awakenings/h (AWN/h), wake after sleep onset (WASO%), sleep efficiency percentage (SE%), percentage of sleep time spent in sleep stages 1 (N1%) and 2 (N2%), slow-wave sleep (N3%), and REM sleep (REM%). Additionally, nocturnal respiratory events such as apnea/hypopnea index (AHI), oxygen desaturation index (ODI), and periodic limb movement index (PLMI) were recorded. Results Neurofibromatosis type 1 children showed a reduction in sleep duration parameters (TST; p < 0.001), sleep efficiency (SE%; p < 0.001), and stage N2% (p < 0.001). Moreover, the number of awakenings per hour (AWN/h), wake after sleep onset (WASO%), and respiratory events such as AHI, ODI, and PLMI resulted higher in NF1 vs. TDC children. Conclusion The data showed that the sleep macrostructure differs between NF1 and TDC children. These findings suggest that the evaluation of sleep may provide useful support in corroborating the diagnosis and offers additional therapeutic management perspectives in NF1 and genetic neurodevelopmental disorders in general.